Endometriosis does not impact aneuploidy rates of products of conception in IVF population - Huijuan Kong; Wenqian Fan; Tian Ye; Linqing Du (Scientific Reports)
Abstract It has been debated whether endometriosis (EMS) adversely affects oocyte quality, potentially leading to a higher incidence of genetically unbalanced embryos or other egg factors that affect the developmental potential. In this study, we explored the effects of endometriosis on risk of chromosomally aberrant in miscarried products of conception (POC) after assisted reproductive treatment (ART), including fresh and frozen cycles. Miscarried POCs were collected from EMS patients (N = 102) and non-EMS patients (N = 441). Single nucleotide polymorphism (SNP) array analysis was conducted on all collected samples. Propensity score matching (PSM, ratio of 1:4) based on maternal age was applied in data analysis. Logistic regression analysis was performed to identify risk factors for chromosomal aberration-induced miscarriage between the two cohorts. A total of 228 (41.99% of 543) conceptuses were identified as having chromosomal aberrations. The results showed that women with EMS had a significantly lower antral follicle count (AFC) (10 ± 5 vs. 14 ± 7, P < 0.01) compared to the control group. Additionally, the EMS group had a relatively lower anti-Mullerian hormone (AMH), higher basal follicle stimulating hormone (FSH) and fewer oocytes, (P > 0.05). There was no significant difference in the chromosomal aberration rate of POCs between EMS and non-EMS groups (35.29% vs. 43.54%; odds ratio (OR) = 1.03, 95% confidence intervals (CIs) 0.79–1.35). This is the first study to show that EMS maybe associated with decreased ovarian reserve, but not related to chromosomal abnormalities in POCs. These results suggest that chromosomal abnormalities may not be the only cause of miscarriage in EMS patients.